EVALUASI KINERJA BUS PATAS ANTAR KOTA DALAM PROPINSI TRAYEK PROBOLINGGO-MALANG - Amal, Andi Syaiful; Sepnawati, Anik (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2013)
Andi Syaiful A. 1) , Anik Sepnawati2)1,2) Jurusan Teknik Sipil Universitas Muhammadiyah MalangAlamat korespondensi : Jl. Raya Tlogomas 246 Malang 65144andiamal99@yahoo.co.idAbstractâ€Bus Patasâ€ is one means of urban transport that is used by people who want toProbolinggo poor or vice versa, its existence is a potential to be served because of theÂ activities that are often carried out by people such as trade, education, social, cultural andÂ others. As a means of transportation bus patas not be separated from the issues affecting theÂ performance of services. Hiatus seat, passenger numbers increased on busy days, theÂ sharpening competition among the fleet on the same route, is an indication of whereÂ conditions require patas bus transportation performance evaluation. There should be a studyÂ to determine the level of performance of freight, transport and analysis needs to strike aÂ balance between demand and supply at the moment.Â This refers to the evaluation study on the performance parameters issued by theDirectorate General of Land Transportation.The evaluation results known load factor average for these Probolinggo-Malang is 0.78,Â the speed of the average travel routes Probolinggo-Malang 45.66 km / h, headway routeÂ Probolinggo-Malang 30.30 minutes, travel time average for these Probolinggo-Malang atÂ 1:31 min / km and the value of the frequency for Probolinggo-Malang route for 1.98 veh /Â hour. And the results of the analysis of the balance between supply and demand obtained theÂ required fleet needs today is 40 fleet.Keywords: public transport, service indicator, total fleet